Structural bioinformatics study of cyclin-dependent kinases complexed with inhibitors - Canduri, Fernanda; da Silveira, Nelson José Freitas; Câmera Junior, João Carlos; de Azevedo Júnior, Walter Filgueira (Eclética Química, 2003)
The present work describes molecular models for the binary complexes CDK9, CDK5 and CDK1 complexed with Flavopiridol and Roscovitine. These structural models indicate that the inhibitors strongly bind to the ATP-binding pocket of CDKs and the structural comparison with the complexes CDK2:Flavopiridol and CDK2:Roscovitine correlates the structural differences with differences in inhibition of these CDKs by the inhibitors. These structures open the possibility of testing new inhibitor families, in addition to new substituents for the already known lead structures such as flavones and adenine derivatives.